Crowdfunding: a promising alternative to turn dreams into reality / Norhafiza Nordin, Faizah Ismail and Zaemah Zainuddin - Nordin, Norhafiza; Ismail, Faizah; Zainuddin, Zaemah (2017)
Crowdfunding, an Internet based fundraising method is gaining popularity for its fast and simpler process. Despite its importance and rapid development, little scholarly literature exists to discuss about this topic. To address this gap, this paper reviews some issues in crowdfunding based on the information gathered from a desktop research. In particular, this paper discusses the crowdfunding’s application, potentials and challenges. Focus is given on how crowdfunding platforms work and their implications both to the founders and funders. How these platforms help to solicit funds from the “crowd” in order to realize projects, which face difficulty to obtain bank loans or any other traditional financing. Using the platforms, an entrepreneur (founder) will be able to obtain external financing from a very large audience. Each individual (funder) will contribute a small amount to raise the targeted amount, enough to finance the project. This method of fundraising saves time and money. Although it offers great potentials and benefits, crowdfunding is not without risk. Since many founders involve start-ups, the risk is quite high. Therefore, rules and regulations must be further developed and implemented in order to protect the interests of both parties (founders and funders).